Out-of-hospital cardiac arrest: Causes according to autopsy and electrocardiography – Analysis of 781 patients with neither hospital care nor prescribed medication during the preceding two years. (May 2020) - Holmgren, C; Abdon, NJ; Bergfeldt, L; Edvardsson, N; Herlitz, J; Karlsson, T; Nyström, B; Åstrand, B
Abstract: Background: There is a knowledge gap regarding aetiology of and potential for predicting out-of-hospital cardiac arrest (OHCA) among individuals who are healthy before the event. Aim: To describe causes of OHCA and the potential for predicting OHCA in apparently healthy patients. Methods: Patients were recruited from the Swedish Register of Cardiopulmonary Resuscitation from November 2007 to January 2011. Inclusion criteria were: OHCA with attempted CPR but neither dispensed prescription medication nor hospital care two years before the event The register includes the majority of patients suffering OHCA in Sweden where cardiopulmonary resuscitation (CPR) was attempted. Medication status was defined by linkage to the Swedish Prescribed Drug Register. Cause of death was assessed based on autopsy and the Swedish Cause of Death Register. Prediction of OHCA was attempted based on available electrocardiograms (ECG) before the OHCA event. Results: Altogether 781 individuals (16% women) fulfilled the inclusion criteria. Survival to 30 days was 16%. Autopsy rate was 72%. Based on autopsy, 70% had a cardiovascular aetiology and 59% a cardiac aetiology. An ECG recording before the event was found in 23% of cases. The ECG was abnormal in 22% of them. Conclusion: Among OHCA victims who appeared to be healthy prior to the event, the cause was cardiovascular in the great majority according to autopsy findings. A minority had a preceding abnormal ECG that could have been helpful in avoiding the event.